(untitled) (LACCEI, 2024)
Nanotechnology has been showing potential applications in various areas of research. Thus, at the crop level, new mechanisms are being found that help the plant in the absorption processes and result in a substantial improvement in the processes of growth speed, improvement of its physiological, biochemical and high biocompatibility traits. The objective of this research was to investigate the influence of the concentration of biogenic zinc oxide nanoparticles (ZnO NPs) on the in vitro germination process in quinoa (Chenopodium quinoa) seeds. The nanoparticles used showed a spherical type geometry and sizes up to 5.36 nm. The results show the stimulation of the nanoparticles in the germination rate between treatments, in addition to a remarkable and better root development. No phytotoxicity samples have been evidenced.